Common mental disorders and perinatal depressive symptoms: an integrative review - Silva,Bruno Pereira da (2020)
ABSTRACT Objective: to investigate occurrence and risk factors for common mental disorders and perinatal depressive symptoms. Methods: an integrative literature review using CINAHL, Embase, PubMed, PsycINFO, and LILACS, looking for studies conducted between 2014 and 2019. Data collection took place between June and July 2019. Health Sciences Descriptors (DeCS) and Medical Subject Heading (MeSH) were used in the search strategies employed in each database. Results: thirteen articles were included. Most studies were conducted in Brazil and with a cross-sectional design. The highest prevalence of common mental disorders (63%) and depressive symptoms (30%) were found in Brazilian studies. Conclusion: high frequencies were found for perinatal mental disorder, with emphasis on studies carried out in Brazil. Low socioeconomic status, being a single mother, history of mental disorder, unplanned pregnancy and multiparity were risk factors for the investigated disorders.